Idiopathic multicentric Castleman disease: A case report - Anna John; Sheima R Das (Asian Journal of Medical Sciences, 2025)
Castleman disease is a rare disease affecting lymph nodes and is considered a non-clonal lymphoproliferative disorder. It has variable clinical presentation and is divided into clinical and histopathological subtypes. Careful evaluation of history and blood investigations contributes to the diagnosis but histopathology remains the precise modality. Treatment involves excision of the affected lymph node in unicentric type of Castleman disease whereas monoclonal antibodies and steroids remain the mainstay of treatment in multicentric Castleman disease. We are presenting a case of 41-year-old female who was on treatment for deep vein thrombosis, presented with generalized lymphadenopathy, investigated for immunoglobulin G4 related disease and lymphoma which was finally proved as idiopathic multicentric Castleman disease.